FEM analysis and experimental validation of flashless cold forging of autonomous underwater vehicle hubs - Khaleed, H.M.T.; Z., Samad; A.R., Othman; M.A., Mujeebu; Hussaini, A.; A.B., Abdullah; Magami, I.B.; Salman Ahmed, N.J.; Quadir, G.A.; Jeevan, Kanesan (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.